2021
DOI: 10.3390/cells10113129
|View full text |Cite
|
Sign up to set email alerts
|

STK11/LKB1 Modulation of the Immune Response in Lung Cancer: From Biology to Therapeutic Impact

Abstract: The STK11/LKB1 gene codes for liver kinase B1 (STK11/LKB1), a highly conserved serine/threonine kinase involved in many energy-related cellular processes. The canonical tumor-suppressive role for STK11/LKB1 involves the activation of AMPK-related kinases, a master regulator of cell survival during stress conditions. In pre-clinical models, inactivation of STK11/LKB1 leads to the progression of lung cancer with the acquisition of metastatic properties. Moreover, preclinical and clinical data have shown that ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…A wide variety of tumors have shown STK11/LKB1 aberrancies [23][24][25]. Genetic anomalies such as loss of heterozygosity, insertion-deletion (indel) mutations, and chromosomal deletions are well-known causes of loss of function in genes [26]. Genetic mapping revealed that STK11 is located on chromosome subband 19p13.3 [27].…”
Section: Stk11/lkb1 Deficiency and Cancermentioning
confidence: 99%
“…A wide variety of tumors have shown STK11/LKB1 aberrancies [23][24][25]. Genetic anomalies such as loss of heterozygosity, insertion-deletion (indel) mutations, and chromosomal deletions are well-known causes of loss of function in genes [26]. Genetic mapping revealed that STK11 is located on chromosome subband 19p13.3 [27].…”
Section: Stk11/lkb1 Deficiency and Cancermentioning
confidence: 99%
“…This is true for patients given with ICI both in first-line and second-line treatments, and considering both monotherapy and a combination of two ICIs ( 168 , 173 , 174 ). However, studies in which the LKB1 mutant tumors’ response to ICI was compared to that of chemotherapy, showed a similarly lower response to both treatments ( 43 , 175 ). Therefore, LKB1 mutations should probably be considered a prognostic factor, independently from the treatment type, rather than a predictive biomarker of ICIs resistance.…”
Section: Lkb1 and Immune Systemmentioning
confidence: 97%
“…In addition, STK11 is also active in modulation of the immune system. Its inactivation promotes the production of proinflammatory cytokines CXCL7, G-CSF and IL-6, which contribute to the accumulation of T cell suppressor neutrophils, with corresponding low CD4+/CD8+ T lymphocyte infiltration and low levels of PD-L1 (programmed cell death-1 ligand) ( 43 47 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KEAP1 mutation prevalence in NSCLC is 15.8% [ 138 ]. Furthermore, STK11/LKB1 and KEAP1 mutations are associated with an inert tumor immune microenvironment, with a reduced density of infiltrating cytotoxic CD8 + T cells and a neutrophil-enriched TME [ 139 ]. STK11/LKB1 - or KEAP1 -mutated NSCLC patients had a higher bTMB than wild-type patients, and KEAP1 -mutated patients had a higher PD-L1 expression (TC ≥ 50%/IC ≥ 50%: 25.00% vs. 14.54%), while STK11/LKB1 -mutated patients had lower PD-L1 expression (TC ≥ 50%/IC ≥ 50%: 7.89% vs. 15.90%) [ 136 ].…”
Section: Tumor/specific Genotypementioning
confidence: 99%